Pengaruh Kredit Macet, Kecukupan Modal dan Likuiditas Terhadap Profitabilitas Bank Pada Bank KBMI 3 Periode 2019-2023 - Moh. Reza Saputra Basiru; Herlina Rasjid; Hais Dama (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to determine the effect of Non-Performing Loans (NPL), Capital Adequacy Ratio (CAR), and Loan-to-Deposit Ratio (LDR) on Bank Profitability (Return on Assets/ROA) in the KBMI 3 banking sector listed on the Indonesia Stock Exchange (IDX) during the period 2019–2023. The sampling technique involved selecting 10 KBMI 3 banking companies. The data collection method used in this study is secondary data, specifically financial reports published by KBMI 3 banking companies on the Indonesia Stock Exchange (IDX). The analysis techniques employed include Multiple Linear Regression Analysis and Descriptive Statistical Analysis using SPSS version 30. Based on the research findings, the partial test results show that Non-Performing Loans (NPL) have a negative and significant effect on Bank Profitability (ROA), Capital Adequacy Ratio (CAR) has a positive and significant effect on Bank Profitability (ROA), while the Loan-to-Deposit Ratio (LDR) has a negative and insignificant effect on Bank Profitability (ROA).